Oxcarts in Mongolian civilization, its construction, usage and phrases - Mijiddorj, Enkhbaatar (Mongolian Journal of Arts and Culture, 2024)
Among Mongolians today, there are very few people who make oxcarts, train their oxes, and move around. Therefore, for all Mongolians, the traditions and usages of making oxcarts, as well as related phrases, are slowly disappearing. In this article, based on the ethnographic research conducted among the Khuvsgul, Zavkhan, and Arkhangai provinces, who live on the back and sides of the Khangai mountain range and still use oxcarts in their daily lives, we will share the tradition of making oxcarts, the types of oxcarts, and the skills of the oxcarters. Монгол соёл иргэншил дэх үхэр тэрэг, түүний хийц, хэрэглээ, үг хэллэг Хураангуй: Өнөөгийн монголчуудын дунд үхэр тэрэг хийж, амбан шараа сурган хөллөж, отор нүүдлийн ая дагаж буй газар тун цөөхөн билээ. Тиймээс нийт монголчуудын хувьд үхэр тэрэг хийх уламжлал, хэрэглээ, түүнтэй холбоотой хэл хэллэгүүд аажим аажмаар алсарч байна. Тус өгүүлэлд Хангай нурууны ар, өврөөр нутаглан, ахуй амьдралдаа үхэр тэргээ ашигласаар буй Хөвсгөл, Завхан, Архангай аймгийнхны дунд хийсэн угсаатны зүйн судалгаанд тулгуурлан үхэр тэрэг хийх уламжлал, үхэр тэрэгний төрлүүд, тэрэгчдийн ур ухаан зэргийг хуваалцах юм. Түлхүүр үгс: биет ба биет бус соёлын өв, үхэр тэрэг, бүтэц, хэрэглээ, үг хэллэг